Happy Valley - Series 3 Episode 1-6 - Harkins, Patrick; Wainwright, Sally; Wainwright, Sally; O'Brien, Fergus; McCready, Dale; McDonnell, Andrew; Perry, Johann; Lancashire, Sarah; Finneran, Siobhan; Norton, James (BBC, 2023)
Sally Wainwright's multi-BAFTA award winning gritty crime drama returns for its final instalment, with Sarah Lancashire, James Norton and Siobhan Finneran reprising their roles. When Catherine discovers the remains of a gangland murder victim in a drained reservoir, it sparks a chain of events that unwittingly leads her straight back to Tommy Lee Royce. Her grandson Ryan is now 16 and still living with Catherine, but he has ideas of his own about what kind of relationship he wants to have with the man Catherine refuses to acknowledge as his father. Still battling the seemingly never-ending problem of drugs in the valley and those who supply them, Catherine is on the cusp of retirement. [Cover]
Keywords: Blu-Ray-Disc